Frotteuristic disorder - a specific paraphilia - Wdowiak, Krystian; Maciocha, Agnieszka; Wąż, Julia; Witas, Aleksandra; Chachaj, Weronika; Winsyk, Aleksandra; Gardocka, Ewa (Quality in Sport, 2025)
Introduction: Frotteuristic disorder is characterized by recurrent and intense sexual arousal from touching or rubbing against a nonconsenting person over a period of at least six months. This behavior is manifested through fantasies, urges, or actions. While many studies indicate that the disorder predominantly affects men, this finding is not universally accepted. Victims of this disorder are typically young women, but only 2.6% of incidents are reported to the police. Most individuals with frotteuristic disorder do not seek treatment voluntarily, often being referred only after committing a crime. Cognitive-behavioral therapy has shown significant therapeutic success, while pharmacological treatments typically involve antiandrogenic medications and drugs that lower sexual drive. Aim of the Study: The aim of this publication is to discuss various aspects of frotteurism based on the latest literature. Material and methods: The PubMed database was searched to find scientific articles in which the terms “frotteurism”, “frotteuristic” or “frotteuristic disorder” appear in the title, abstract, or keywords. Conclusions: There are gaps in research, including underestimation of prevalence, gender differences, and unclear etiological factors. Further studies could lead to better understanding and improved treatments for individuals with frotteuristic disorder. Additionally, the etiology of the disorder remains unclear. Further research could help clarify the causes of frotteurism, potentially leading to more effective treatments for individuals affected by this paraphilia.